(untitled) (International Journal of Physiotherapy, 2021)
Background and purpose: Prechtl’s general movement assessment is a tool to identify infants at risk of abnormal neurodevelopmental outcomes especially cerebral palsy. There is a need for further studies to establish its effectiveness in clinical practice. The main objective of this study was to find the diagnostic accuracy of prechtl’s general movement assessment to predict neuromotor outcomes of preterm babies at one year corrected age when done in a standard clinical practice setting. The secondary objective was to find the inter-rater reliability of general movement assessment between two raters in a clinical setting. Methods: 116 preterm infants (55 females and 61 males) born below gestational age 35 weeks participated in this study. Prechtl’s general movement assessment was done at two points of time – once between 33 to 40 weeks post menstrual age and later between 3 to 4 months corrected age. Babies were reassessed at 12 months (±1week) corrected age using the Infant Neurological International Battery and Alberta Infant Motor Scale to identify neuromotor dysfunction. To find the inter-rater reliability, 75 video recordings at preterm/term age and 73 recordings at fidgety age were viewed and rated independently by two raters. Results: Statistical analysis using the Fishers’ exact test and Pearson’s chi-square test showed significant association (p<.001) between Prechtl’s General movement assessment and neuromotor outcomes at one year corrected age. General movement assessment at preterm age and fidgety age showed sensitivity of 85% (each) , specificity of 85% & 99%, positive predictive value of 27% & 85 %, and negative predictive value of 98% & 99% respectively in predicting neuromotor outcomes. Substantial agreement was found between two trained raters. Kappa values were 0.78 and 0.72for assessments done at preterm/ term age and three months corrected age respectively. Conclusion: The results suggest that Prechtl’s general movement assessment done in routine clinical settings can reliably predict neuromotor outcomes of premature babies at one year corrected age. Thus, it has practical applications to identify premature babies at high risk of abnormal neurodevelopment in infancy.